(untitled) - Kennedy, Michael (New Jersey, 2006)
This book serves both as a general introduction to geographic information systems (GIS) and as a manual for a variety of functions of the ArcGIS Desktop applications. The exercises are full of useful, valuable hints and tricks that are not always found in other manuals and handbooks
Keywords: Geographic information systems,ArcGIS,Hệ thống thông tin địa lý,ArcGIS